Chapter 25 Process Tracing An Analyticist Approach - van Meegdenburg, Hilde (Taylor & Francis, 2023)
This contribution develops process tracing (PT) as a method for Foreign Policy Analysis (FPA). It explains what it takes to conduct PT, trace a mechanism, and draw conclusions on that basis. Importantly, I lay out an analyticist approach to PT that is amendable to more actor-centered and interpretivist studies. This approach treats mechanisms as akin to Weberian ideal types: abstract constructs that are adduced from multiple concrete, contextually embedded, and largely idiosyncratic instantiations. This creates space for agency and contingency and allows us to a) study how a mechanism or concatenation of mechanisms led to a particular outcome; b) assess how the mechanism(s) functioned in a given context; and c) abstract from the specific instantiation(s) more general propositions about foreign policy making. In an empirical example of state employment of Private Military and Security Contractors, drawing on interpretivist and narrative-based understandings of FPA, I illustrate what this means in practice.